"All Patients Are Not Treated as Equal": Extending Medicine's Social Contract to Black/African American Communities. Issue 3 (14th June 2022) - Rockich-Winston, Nicole; Taylor, Taryn R.; Richards, Joslyn A.; White, DeJuan; Wyatt, Tasha R.
Abstract: Phenomenon: The social contract is an implicit agreement that governs medicine's values, beliefs, and practices in ways that uphold the profession's commitment to society. While this agreement is assumed to include all patients, historical examples of medical experimentation and mistreatment suggest that medicine's social contract has not been extended to Black patients. We suggest that is because underlying medicine's contract with society is another contract; the racial contract, which favors white individuals and legitimizes the mistreatment of those who are nonwhite. When Black/African American physicians enter medicine, they enter into the social contract as an agreement with society, but must navigate the realities of the racial contract in ways that have yet to be acknowledged. This study examines how Black/African American physicians interpret and enact the social contract in light of the country's racial contract by investigating the ways in which Black/African American physicians discuss their interactions with Black patients. Approach: This qualitative study reexamines cross-sectional data previously collected in 2018-2019 examining the professional identity formation (PIF) experiences of Black/African American trainees and physicians in the Southern part of the U.S. The goal of the larger study was to explore participants' professional identity formation experiences as racialized individuals within a predominantly white profession. The current study examines these data in light of medicine's social contract with society and Mill's (1997) theory of the racial contract to understand how Black physicians interpret and enact the social contract. Participants included 10 Black/African American students, eight residents, and nine attending physicians. Findings: The findings show that Black/African American physicians and trainees are aware of the country's racial contract, which has resulted in Black patients being historically excluded from what has been described in the social contract that governs all physicians. As such, they are actively working to extend the social contract so that it includes Black patients and their communities. Specifically, they engage in trust building with the Black community to make sure all patients are included. Building trust includes ensuring a consistent stream of new Black/African American trainees, and equipping Black trainees and patients with the skills needed to improve the healthcare within the Black/African American community. Insights: While it been has assumed that all patients are included in the social contract between medicine and society, historical examples of medical mistreatment and experimentation demonstrate this is inaccurate; Black/African American communities have not been included. In an effort to dismantle systemic racism in the U.S., medical education must teach about its racist past and divulge how some communities have been historically excluded, providing new ways to think about how to include everyone in medicine's social contract.